PEMBUATAN PADUAN INTERMETALIK Mg2Si DENGAN DOPING BISMUTH SEBAGAI MATERIAL TERMOELEKTRIK: Synthesis of Bismuth Doped Mg2Si Intermetallic Alloy as a Thermoelectric Material - Adi Chandra, Septian; Saprila Suherman, Mila; Tjahjono, Arif; Roberto, Rahadian; Pria Utama, Dedi; Noer Syahid, Adi; Yunan Hasbi, Muhammad; Dwi Yudanto, Sigit (Universitas Negeri Jakarta, 2024)
Increasing efficiency in gasoline fuel consumption in motorized vehicles is currently continuing. One way this is done is by making use of the energy that is lost during the combustion of a motorcycle engine. About half of the energy produced during burning will be lost due to heat energy and exhaust gases. This waste heat can be utilized by converting it into another form of energy. Thermoelectric materials are those that can convert heat energy into electricity directly. Thus, in this work, we synthesized the bismuth-doped Mg2Si thermoelectric material using a solid-state reaction method using a powder in a sealed tube technique. The initial step in the production process involves measuring the raw materials bismuth, silicon, and magnesium using the Mg2Si1-xBix formula (x = 0.00, 0.025, and 0.045). The raw material powder is grinded in a shaker mill before being sealed in a stainless steel tube. The powder is sealed in a tube and heated to 800 °C for 6 hours. According to XRD test results, the Mg2Si phase and Si and MgO phases have formed. The lattice constant of the cubic Mg2Si phase was found at 0.636 nm. A SEM investigations of surface morphology suggest that bi-doping on Si sites influences grain size refinement. Therefore, it can be concluded that the Mg2Si intermetallic alloy production process was successfully completed.